1997
DOI: 10.1007/bf02050938
|View full text |Cite
|
Sign up to set email alerts
|

Posterior sagittal anorectoplasty: Primary repair of a rectovaginal fistula in an adult

Abstract: Posterior sagittal anorectoplasty can be successfully performed in the adult patient for a primary repair of anorectal malformations. This operation should be considered in patients who have undergone another prior operative procedure with less than optimum function and now desire a secondary corrective procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Although the total number of patients in the literature who underwent primary repair is not many, most authors have reported good results, some of them anecdotal in adults with rectovaginal fistula [10,11]. In the largest study reported so far, 47 patients with rectovestibular fistula underwent fistula transposition without colostomy [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although the total number of patients in the literature who underwent primary repair is not many, most authors have reported good results, some of them anecdotal in adults with rectovaginal fistula [10,11]. In the largest study reported so far, 47 patients with rectovestibular fistula underwent fistula transposition without colostomy [12].…”
Section: Discussionmentioning
confidence: 99%
“…Though PSARP suggested by Pena et al continues to be the treatment of choice for ARM in children, in adult due to extreme rarity of incidence there is no recommended treatment and possibility of PSARP is yet uncertain [ 4 ]. There are isolated case reports of anorectal malformation in adults treated successfully with PSARP [ 4 , 5 ] but this approach involves surgically dividing the puborectalis component of levator muscles and muscle complex (which play a very important role in the continence mechanisms [ 6 ]), perineal body, and the perineal skin. This can cause wound complications like scar of the perineal skin bridge between the fistula and the new anus [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with this anomaly can continue to pass stools through vagina and can reach adult age group with only complaint of incontinence. There are very few case reports in literature of presentation of such anomalies in the postadolescent age group [3,7]. Ideal treatment and long-term results in such cases are unknown.…”
Section: Discussionmentioning
confidence: 99%